2006
DOI: 10.3177/jnsv.52.437
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Broccoli (Brassica oleracea) against Oxidative Damage in Vitro and in Vivo

Abstract: SummaryThe antioxidative effect and protective potential against diabetes of the broccoli flower were investigated both in vitro and in a diabetic rat model. Among fractions of MeOH, CH 2 Cl 2 , BuOH, and H 2 O, the BuOH fraction exerted the strongest inhibitory activities on 1,1-diphenyl-2-picrylhydrazyl radical, radical-induced protein oxidation, and nitric oxide generation by sodium nitroprusside. The in vitro results suggest that the BuOH fraction from the broccoli flower has a protective potential against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…In one study, administration of 100 g/d fresh broccoli sprouts in healthy subjects reduced urinary 8-isoprostane and plasma phosphatidylcholine hydroperoxide and increased CoQ 10 H2 (reduced form of coenzyme Q 10 )/coenzyme Q 10 ratio as an effective inhibitor of oxidative damage in LDL (Menke et al, 2004;Murashima et al, 2004). In addition, oral administration of 100 or 200 mg/kg broccoli extract in diabetic rats resulted in significant reduction in serum thiobarbituric acid-reactive substances (Cho et al, 2006). Administration of 200 mg/d dried broccoli sprouts in rats decreased oxidative stress as shown by increased glutathione as a critical antioxidant for scavenging peroxides and other lipid derived oxidant (Wu and Juurlink, 2001;Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, administration of 100 g/d fresh broccoli sprouts in healthy subjects reduced urinary 8-isoprostane and plasma phosphatidylcholine hydroperoxide and increased CoQ 10 H2 (reduced form of coenzyme Q 10 )/coenzyme Q 10 ratio as an effective inhibitor of oxidative damage in LDL (Menke et al, 2004;Murashima et al, 2004). In addition, oral administration of 100 or 200 mg/kg broccoli extract in diabetic rats resulted in significant reduction in serum thiobarbituric acid-reactive substances (Cho et al, 2006). Administration of 200 mg/d dried broccoli sprouts in rats decreased oxidative stress as shown by increased glutathione as a critical antioxidant for scavenging peroxides and other lipid derived oxidant (Wu and Juurlink, 2001;Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrate that SFN reduces oxidative stress through the activation of antioxidant response pathways (Piao et al, 2005;Xue et al, 2008;Zhu et al, 2008). Animal studies have reported that supplementation with broccoli sprouts, containing SFN, resulted in attenuation of oxidative stress and inflammation (Wu et al, 2004;Cho et al, 2006). In addition, oral administration of broccoli extract in diabetic rats led to significant decrease in oxidative stress through the inhibition of lipid peroxidation (Piao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The control group rats were untreated. The four treated groups received CdCl 2 in a dose of 0.2 mg/kg, [Yang et al 2000] subcutaneously; CdCl 2þ sulforaphane 25 mg/rat [Cho et al 2006], CdCl 2þ vitamin E 75 mg/kg [Adaikpoh and Obi 2009], and CdCl 2þ plant extract 100 mg/kg [Kirana et al 2009] by gastric intubation using a feeding tube for 15 d. On the last day of experimentation, final body weight of each animal was recorded and rats were given short anesthesia with chloroform and sacrificed from ventral side. All of the study and animal sacrifice procedures were approved by the university animal sciences department ethical committee.…”
Section: Experimental Designmentioning
confidence: 99%
“…These effects of broccoli components may be partly related to their direct ability to scavenge reactive oxygen species (ROS) [33,34]. Some of the broccoli components at high levels, such as vitamin C, are recognised for this property.…”
Section: Antioxidant and Detoxification Mechanismsmentioning
confidence: 99%